Determining The Crystallite Size of TiO2/EG-Water XRD Data Using the Scherrer Equation - Muhamad Taufik Ulhakim; Sukarman Sukarman; Khoirudin Khoirudin; Nazar Fazrin; Tomas Irfani; Afif Hakim (Department of Physics, Sebelas Maret University, 2024)
X-ray diffraction (XRD) data and the Scherrer equation were utilized to analyze the crystallite Size of titanium dioxide (TiO2) in a solution of ethylene glycol (EG) and distilled water. The XRD analysis was conducted using a Rigaku Miniflex 600 instrument with an X-ray wavelength of approximately 0.15046 nm. The examination yielded the full-width half maximum (FWHM), which was subsequently examined using the Scherrer equation. This experiment employed TiO2 with a purity level of 99.8% and a crystal Size of 30 nm. The analysis revealed that the average crystallite Size of TiO2 in the sample is 19.45 nm, with the highest measurement at about 30.38 nm. The Spearman correlation equation was employed to validate the outcomes. The Spearman's correlation coefficient between the FWHM variable and the crystallite Size of TiO2 nanoparticles is -0.958. These findings shed light on the crystal structure of TiO2 under these conditions. These findings lend support to the use of TiO2 in a variety of nanotechnology applications. However, more research is needed to understand fully how crystallite-Size TiO2 nanoparticles work in different settings and to find the best ways to prepare samples, including understanding the specific phase and how it affects the stability of fluids. This research contributes significantly to the understanding of the properties of TiO2 in a solution of distilled water and EG, as well as to the characterization of nanomaterials, with particular emphasis on issue 9 of the SDGS Goal concerning industry, innovation, and infrastructure.